Respuesta :
Answer:
B
Step-by-step explanation:
Our equation is x² + 7x - 4 = 0. We need to use the quadratic formula, which states that for a quadratic formula of the form ax² + bx + c = 0, then the zeroes/solutions are: [tex]x=\frac{-b+\sqrt{b^2-4ac} }{2a}[/tex] or [tex]x=\frac{-b-\sqrt{b^2-4ac} }{2a}[/tex].
Here, a = 1, b = 7, and c = -4. Plug these in:
[tex]x=\frac{-b+\sqrt{b^2-4ac} }{2a}[/tex]
[tex]x=\frac{-7+\sqrt{7^2-4*1*(-4)} }{2*1}=\frac{-7+\sqrt{49+16} }{2} =\frac{-7+\sqrt{65} }{2}[/tex]
OR
[tex]x=\frac{-b-\sqrt{b^2-4ac} }{2a}[/tex]
[tex]x=\frac{-7-\sqrt{7^2-4*1*(-4)} }{2*1}=\frac{-7-\sqrt{49+16} }{2} =\frac{-7-\sqrt{65} }{2}[/tex]
Thus, the answer is B.
Answer:
Option 2
x equals negative 7 plus or minus the square root of 65, all over 2
Step-by-step explanation:
x² + 7x - 4 = 0
x = [-b +/- sqrt(b²-4ac)]/2a
x = [-7 +/- sqrt(7² - 4(1)(-4)]/2
x = [-7 +/- sqrt(65)]/2